(untitled) (Rabi Sangyan, 2024)
The study aims to investigate the relationship between supervisory behavior and job stress among employees in these banks, specifically examining effects of role clarity, communication, delegation, motivation, and social support. A survey-based research design was implemented, involving a sample of 210 respondents. Correlation and regression were used. The overall job stress mean score is 3.96, with high agreement on supervisor support (4.47) but lower scores for work-life balance (2.94). Role clarity scores a strong 4.35, indicating clear job expectations that help reduce stress. Communication is also effective, with a mean of 4.42, enhancing employee morale. Delegation practices received a score of 4.36, particularly regarding workload management. Motivation is notable at 4.38, highlighting appreciation and learning opportunities that mitigate stress. Lastly, social support averages 3.96, with many feeling a sense of belonging, although some report feelings of exclusion (2.94). The study successfully identifies key dimensions of supervisory behavior that impact job stress in Nepalese commercial banks. Enhancing role clarity and communication within supervisor-subordinate relationships may alleviate job stress, contributing to improved employee well-being and organizational performance.